A job demands-resources perspective on salespersons' market intelligence activities in new product development. Issue 1 (2nd January 2016) - Kuester, Sabine; Rauch, Andreas
Abstract : Research shows that R&D's use of sales' market intelligence positively influences innovation performance. However, little is known about whether this effect hinges on salespersons' engagement towards and perceptions of market intelligence activities (MIA). Moreover, research remains incomplete regarding the drivers of salespersons' MIA engagement. Using dyadic data from 359 salespersons and 239 R&D managers in a multi-level model based on the job demands-resources theory, we demonstrate that the positive effect of R&D's use of sales' market intelligence on innovation performance is especially pronounced when salespersons' market intelligence generation is high and role ambiguity is low. We also show that although salespersons' self-set MIA goals are a strong driver of their MIA engagement, not assigning salespersons MIA goals may be a double-edged sword: in the short run, salespersons might engage in MIA voluntarily. However, in the long run, they could incur psychological costs in terms of role ambiguity and conflict, preventing them from engaging in MIA.